2000
DOI: 10.1074/jbc.m005869200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Protein Kinase C and cAMP-dependent Pathways in the Phosphorylation of the Na,K-ATPase

Abstract: To test the hypothesis that there is cross-talk between the protein kinase C (PKC) and protein kinase A (PKA) pathways in the regulation of the Na,K-ATPase, we measured its phosphorylation in mammalian cell cultures. Phosphorylation of the PKC site, Ser-18, appeared to be due to the activation of the ␣ isoform of the kinase. In NRK-52E and L6 cells, this phosphorylation was reduced by prior activation of a cAMP-dependent signaling pathway with forskolin. In principle this would be consistent with direct intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 62 publications
3
47
0
Order By: Relevance
“…Unlike PP1, PP2A is not a classical target for cAMP action, although reports exist describing cAMP-dependent PP2A activation (75,76); however, the mechanistic details for cAMP stimulation of PP2A are still unknown. PP2A is a major serine/ threonine phosphatase involved in cell signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike PP1, PP2A is not a classical target for cAMP action, although reports exist describing cAMP-dependent PP2A activation (75,76); however, the mechanistic details for cAMP stimulation of PP2A are still unknown. PP2A is a major serine/ threonine phosphatase involved in cell signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A few other studies have suggested that PP2A can be activated by forskolin (14,32), a drug normally associated with activation of adenylyl cyclase and generation of cAMP. However, those studies suggested an indirect role for forskolin that did not depend on PKA, and perhaps did not depend on cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…1A suggests that effects are not sustained long term. This may reflect a cellular homeostatic response to activation of cAMP-dependent signaling that terminates a phosphorylation-dependent part of the signal as discussed previously (37). For the variable we measure here, mechanisms that inactivate the downstream oxidative signaling pathway or directly activate deglutathionylation may have addi-FIGURE 5.…”
Section: Namentioning
confidence: 99%